Penatalaksanaan Holistik pada Pasien Lansia Dengan PPOK dan Hipertensi Melalui Pendekatan Kedokteran Keluarga di Puskesmas Kalirejo - Khairunnisa, Lyliani; Angraini, Dian Isti; Harmaina, Harmaina (CV. Jasa Sukses Abadi, 2024)
Chronic Obstructive Pulmonary Disease (COPD) and Hypertension is a non-communicable disease which become a health problem globally and in Indonesia. COPD and Hypertension can be controlled through a healthy lifestyle which support from family and community is needed, therefore it is important to carry out holistic management through a family approach to patients. This study is a case report. Primary data were obtained through anamnesis from the patient's family, physical examination, and home visits to assess the physical environment. The assessment is based on a holistic diagnosis from the beginning, process, and end of the study. The results, Mr. E is 64 years old, with COPD and history of uncontrolled hypertension in the past 10 years. Internal risk factors include a history of smoking in the past 30 years and lack of knowledge about the disease. External risk factors are the lack of knowledge of the patient's family about the patient's disease, smoking behavior in the home by other family members and the patient's workplace with a lot of exposure to smoke. Interventions were carried out in the form of education. After the intervention, changes in patient knowledge, blood pressure, CAT Score and lifestyle were obtained. The diagnosis in this patient complies with the national guidelines. The management given is in accordance with the guidelines, there is a change in knowledge of the patient and the patient's family after the intervention is carried out by providing counseling based on evidence-based medicine which is patient centered and a family approach.